ANALYSIS OF SOFTWARE QUALITY USING THE FURPS+ MODEL - Puspita, Safriya Murni; Ardhani, Alvina Waihda; Retnaningrum, Dea Ayu; Firmansyah, Afreza Restu; Rolliawati, Dwi (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2024)
Abstract: Software quality analysis is essential to ensure applications are reliable, efficient, and meet user needs. The FURPS+ model (Functionality, Usability, Reliability, Performance, Supportability, plus) provides a comprehensive framework for evaluating software quality. This study analyzes the implementation of Software Quality Assurance (SQA) in the SKEK UINSA application, a Learning Management System (LMS) designed to record extracurricular activities of UINSA students. With 100 respondents (lecturers, students, and alumni), the research employs a quantitative approach to examine both functional and non-functional aspects. The results show that functionality and usability aspects scored an average of 71%, reliability 66%, performance 61%, supportability 79%, and additional factors (plus) 64%. Overall, the SKEK UINSA application demonstrates good quality in terms of functionality, ease of use, performance, and flexibility. Keywords: FURPS+; Reliability; SKEK; Validity; Quantitative Method  Abstrak: Analisis kualitas perangkat lunak penting untuk memastikan aplikasi andal, efisien, dan sesuai kebutuhan pengguna. Model FURPS+ (Functionality, Usability, Reliability, Performance, Supportability, plus) menawarkan kerangka komprehensif untuk evaluasi kualitas perangkat lunak. Penelitian ini menganalisis penerapan Software Quality Assurance (SQA) pada aplikasi SKEK UINSA, aplikasi semacam LMS (Learning Management System) untuk mencatat kegiatan ekstrakurikuler mahasiswa UINSA. Dengan 100 responden (dosen, mahasiswa, dan alumni), penelitian menggunakan pendekatan kuantitatif untuk mengkaji aspek fungsional dan non-fungsional. Hasilnya, aspek functionality dan usability memiliki persentase rata-rata 71%, reliability 66%, performance 61%, supportability 79%, dan faktor tambahan (plus) 64%. Secara keseluruhan, aplikasi SKEK UINSA menunjukkan kualitas baik dalam fungsi, kemudahan penggunaan, kinerja, dan fleksibilitas. Kata kunci: FURPS+;  Metode Kuantitatif ; SKEK; Validitas; Reliabilitas